Assessment of Organisational Change Project based on Six Box Model: A Case Study of High-Tech Enterprise in China - Yu, Wei (Asia Pacific Economic and Management Review, 2025)
Organisational change is regarded as the process of transforming structure and function of the organisations to adapt operations to external business environment with full of uncertainty. The purpose of this paper is to assess organisational change project based six box model as the organisational diagnose technique. A case study is undertaken in a high-tech enterprise in China, Lezhichen Technology, regarding their change initiative by project for further improvement and deeper collaborations with clients. It presents the change overview includes stakeholder analysis, drivers and constraints, cost and benefit analysis together with the change assessment and evaluation. The findings indicate that the outcome of organisational change project is linked with the contributions of both strategic organisational and certain human resource practices. Understanding the potential challenges and strategies can support managers implement the organisational change project in a more effective approach.